2007
DOI: 10.1037/0022-006x.75.5.765
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of prize-based reinforcement density for simultaneous abstinence from cocaine and heroin.

Abstract: To examine the effect of reinforcer density in prize-based abstinence reinforcement, heroin/cocaine users (N = 116) in methadone maintenance (100 mg/day) were randomly assigned to a noncontingent control group (NonC) or to 1 of 3 groups that earned prize draws for abstinence: manual drawing with standard prize density (MS) or computerized drawing with standard (CS) or high (CH) density. Probabilities (prizes/draw) were standard (50%) and high (78%); prize density was double blind. Mean prize values were CH, $2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 43 publications
0
22
1
Order By: Relevance
“…Finally, although the present study design allowed a comparison between the two CM strategies and against drug use early in treatment, the inclusion of a noncontingent control group would have provided additional comparative information on the overall effect sizes of the CM interventions. A noncontingent group in the larger clinical trial (Ghitza et al, 2007) that we conducted immediately after this pilot study appeared to show less abstinence than was seen here, though of course the groups cannot be directly compared.…”
Section: Discussioncontrasting
confidence: 77%
“…Finally, although the present study design allowed a comparison between the two CM strategies and against drug use early in treatment, the inclusion of a noncontingent control group would have provided additional comparative information on the overall effect sizes of the CM interventions. A noncontingent group in the larger clinical trial (Ghitza et al, 2007) that we conducted immediately after this pilot study appeared to show less abstinence than was seen here, though of course the groups cannot be directly compared.…”
Section: Discussioncontrasting
confidence: 77%
“…Some (e.g., Ghitza et al, 2007; Petry & Martin, 2002; Petry, Martin, & Simcic, 2005), but not all (e.g., Petry et al, 2007; Rawson et al, 2002; Silverman et al, 1999), studies of CM in methadone clinics found significant benefits of CM on abstinence after CM ended. This study found a trend for SC patients to submit more negative samples at follow-up than CM patients.…”
Section: Discussionmentioning
confidence: 99%
“…They have been shown to be important indicators of treatment success (Sorensen and Copeland, 2000;Teichner et al, 2001;Hudson et al, 2002;Kampman et al, 2004). To have adequate statistical power, we combined data from two of our clinical trials evaluating the efficacy of CM for heroin/cocaine abuse Ghitza et al, 2007Ghitza et al, , 2008. Each participant was enrolled in only one of the clinical trials.…”
Section: Introductionmentioning
confidence: 99%